2015
DOI: 10.1002/jso.23900
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil‐lymphocyte and platelet‐lymphocyte ratio in patients after resection for hepato‐pancreatico‐biliary malignancies

Abstract: Elevated NLR and PLR were predictors of worse long-term outcome among patients with HPB malignancy undergoing resection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(48 citation statements)
references
References 51 publications
2
45
1
Order By: Relevance
“…Additionally the Garcea et al40 study highlighted the characteristics of the preoperative NLR to be useful as a significant prognostic marker regarding disease-free survival following curative resection of pancreatic ductal adenocarcinoma in contradiction to the PLR alone. On the other hand, Spolverato et al41 from the John Hopkins group reported that the elevated NLR and PLR were predictors of considerably worse long-term outcomes among patients with a HPB malignancy who are undergoing resection, including a proposed pancreatic ductal adenocarcinoma, however the ratios were calculated within 30 days prior to surgery, with a large percentage of the patient population having received neo-adjuvant chemotherapy though. As stated above, we therefore calculated the NLR and PLR within 10 days to the use of a neoadjuvant chemotherapy/chemoradiation, or within 10 days prior to surgery, for patients who did not receive the proposed neoadjuvant chemotherapy/chemoradiation.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally the Garcea et al40 study highlighted the characteristics of the preoperative NLR to be useful as a significant prognostic marker regarding disease-free survival following curative resection of pancreatic ductal adenocarcinoma in contradiction to the PLR alone. On the other hand, Spolverato et al41 from the John Hopkins group reported that the elevated NLR and PLR were predictors of considerably worse long-term outcomes among patients with a HPB malignancy who are undergoing resection, including a proposed pancreatic ductal adenocarcinoma, however the ratios were calculated within 30 days prior to surgery, with a large percentage of the patient population having received neo-adjuvant chemotherapy though. As stated above, we therefore calculated the NLR and PLR within 10 days to the use of a neoadjuvant chemotherapy/chemoradiation, or within 10 days prior to surgery, for patients who did not receive the proposed neoadjuvant chemotherapy/chemoradiation.…”
Section: Discussionmentioning
confidence: 99%
“…In a study of 452 patients who underwent a HPB procedure for malignant disease, NLR >5 was found to be associated with worse OS. 23 Elevated NLR is associated with worse survival after hepatectomy for intrahepatic cholangiocarcinoma. 24,25 Elevated preoperative NLR is associated with worse OS in gallbladder cancer at a lower threshold (>1.94) than the current study according to at least one other group of investigators.…”
Section: Discussionmentioning
confidence: 99%
“…For the purposes of this study NLR greater than or equal to 5 was defined as elevated. 8,17,23,24 Postoperative complications were manually extracted from each patient's chart at each institution and entered into the standardized data collection sheet. If no complication was experienced, nothing was noted.…”
Section: Study Population and Data Collectionmentioning
confidence: 99%
“…PLR was calculated as the platelet count divided by the lymphocyte count. NLR < 2 was considered low risk, 2-5 moderate risk, and > 5 high risk (14,20). Although cutoff PLR values of 190-244 have been used in previous studies, the precise PLR cutoff has not been well defined (20,21).…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies investigated the use of NLR and PLR in diabetes mellitus, acute coronary syndrome, ulcerative colitis, end-stage renal disease, tuberculosis, rheumatoid arthritis, cirrhosis, and systemic inflammation in familial Mediterranean fever. In addition, there have been studies proposing that NLR and PLR can be used to determine prognoses in cancer patients (13)(14)(15)(16)(17)(18)(19)(20). Few studies have evaluated NLR and PLR in psoriasis patients (16)(17)(18).…”
Section: Introductionmentioning
confidence: 99%